Big Data Authentication Protocol with Hierarchical Attribute-Based Encryption and Authorization Structure - Tuase, SE; Matthias, D; Nwiabu, ND (International Journal of Computer Sciences and Engineering, 2020)
The term big data arose under the explosive increase of global data as a technology that is able to store and process big and varied volumes of data, providing both enterprises and science with deep insights over its clients’ experiments. Big Data provides a reliable, fault-tolerant, available and scalable environment to harbor big data distributed management systems thus provide a need store our data at cloud providers plaion and authorization structure of cloud big data access control system that will authenticate authorities or users. Our proposed protocol resorts to tree-based signature to significantly improve the security of attribute authorization thus providing data owner a level of security on the data that will require at least two-level of attributes been satisfy before big data can be access. To satisfy big data requirements, we proposed authentication protocol that support two levels of hierarchical attribute-based encryption and authorization structure using a combination of advanced encryption standard (AES), elliptic curve cryptography combining with the hardness of Diffie Hellman theorem (ECDH). Often times, data and file access control encryption were usually implemented with RSA and DSA protocol, which also comes with their own attendant problems, such as computational overhead cost, time sequence for both encryption and decryption key, encryption keys bit length which also culminate in longer period of time for process execution, We proposed a protocol for authentication and key exchange using AES (Advance Encryption Standard) and ECDH (Elliptic Curve Diffie Hellman) that help to resist forgery attack, replay attack, short key bits length thereby enable less utilization of bandwidth and availability on both mobile and desktop computing with robust security based on hardness of Diffie Hellman and Elliptic Curve cryptography algorithm. In addition, we proposed protocol that help preserve entities privacy, our protocol performance is far better than existing protocol, ours enable less power consumption and low bandwidth consumption as its key length invariably has lower bits than other protocol bits lengths.